Dysregulated complement activation during acute myocardial infarction leads to endothelial glycocalyx degradation and endothelial dysfunction via the C5a:C5a-Receptor1 axis - Vahldieck, Carl; Löning, Samuel; Hamacher, Constantin; Fels, Benedikt; Rudzewski, Bettina; Nickel, Laura; Weil, Joachim; Nording, Henry; Baron, Lasse; Kleingarn, Marie; Karsten, Christian Marcel; Kusche-Vihrog, Kristina (Frontiers in Immunology, 2024)
Introduction: Complement-mediated damage to the myocardium during acute myocardial infarction (AMI), particularly the late components of the terminal pathway (C5-convertase and C5b-9), have previously been characterized. Unfortunately, only few studies have reported a direct association between dysregulated complement activation and endothelial function. Hence, little attention has been paid to the role of the anaphylatoxin C5a. The endothelial glycocalyx (eGC) together with the cellular actin cortex provide a vasoprotective barrier against chronic vascular inflammation. Changes in their nanomechanical properties (stiffness and height) are recognized as hallmarks of endothelial dysfunction as they correlate with the bioavailability of vasoactive substances, such as nitric oxide (NO). Here, we determined how the C5a:C5aR1 axis affects the eGC and endothelial function in AMI. Methods: Samples of fifty-five patients with ST-elevation myocardial infarction (STEMI) vs. healthy controls were analyzed in this study. eGC components and C5a levels were determined via ELISA; NO levels were quantified chemiluminescence-based. Endothelial cells were stimulated with C5a or patient sera (with/without C5a-receptor1 antagonist "PMX53") and the nanomechanical properties of eGC quantified using the atomic force microscopy (AFM)-based nanoindentation technique. To measure actin cytoskeletal tension regulator activation (RhoA and Rac1) G-LISA assays were applied. Vascular inflammation was examined by quantifying monocyte-endothelium interaction via AFM-based single-cell-force spectroscopy. Results: Serum concentrations of eGC components and C5a were significantly increased during STEMI. Serum and solely C5a stimulation decreased eGC height and stiffness, indicating shedding of the eGC. C5a enhanced RhoA activation, resulting in increased cortical stiffness with subsequent reduction in NO concentrations. Monocyte adhesion to the endothelium was enhanced after both C5a and stimulation with STEMI serum. eGC degradation-and RhoA-induced cortical stiffening with subsequent endothelial dysfunction were attenuated after administering PMX53. Conclusion: This study demonstrates that dysregulated C5a activation during AMI results in eGC damage with subsequent endothelial dysfunction and reduced NO bioavailability, indicating progressively developing vascular inflammation. This could be prevented by antagonizing C5aR1, highlighting the role of the C5a:C5a-Receptor1 axis in vascular inflammation development and endothelial dysfunction in AMI, offering new therapeutic approaches for future investigations.